1983
DOI: 10.1016/s0022-5347(17)51137-4
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis of the Ureter can Present as Renal Failure: A Case Report and Review of Endometriosis Affecting the Ureters

Abstract: Of the female subjects with pelvic endometriosis 1.2 per cent are found to have involvement of the genitourinary tract. Ureteral obstruction secondary to endometriosis is uncommon and usually is unilateral. We report a case of renal failure with hypertension due to bilateral ureteral obstruction from pelvic endometriosis. Ureteral endometriosis and its treatment are discussed. In premenopausal women presenting with bilateral obstruction of the distal ureters endometriosis should be part of the differential dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

1987
1987
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 9 publications
0
4
0
3
Order By: Relevance
“…Renal impairment is transient provided that percutaneous drainage is achieved or early surgery is performed. Interestingly, studies have demonstrated that more than half of patients with ureteral obstruction secondary to endometriosis are asymptomatic 3,9 , 14 . Hormonal therapy is not recommended in ureteral endometriosis, while extensive endometriosis requires multidisciplinary management 3,9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal impairment is transient provided that percutaneous drainage is achieved or early surgery is performed. Interestingly, studies have demonstrated that more than half of patients with ureteral obstruction secondary to endometriosis are asymptomatic 3,9 , 14 . Hormonal therapy is not recommended in ureteral endometriosis, while extensive endometriosis requires multidisciplinary management 3,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal therapy is not recommended in ureteral endometriosis, while extensive endometriosis requires multidisciplinary management 3,9 . Early surgical (open or laparoscopic) excision of the ureteral and periureteral lesion, together with relevant ureteral reconstruction and re‐implantation is recommended whenever necessary 3,9 , 14–16 …”
Section: Discussionmentioning
confidence: 99%
“…La gravité de l'atteinte urétérale repose sur son caractère paucisymptomatique avec une destruction à bas bruit du parenchyme rénal, l'évolution pouvant se faire vers l'insuffisance rénale terminale [5]. Des cas ont été décrits de révélation d'endométriose urétérale sous forme de décom-pensation sur le mode d'insuffisance rénale aiguë [6].…”
Section: Symptomatologie Urinaireunclassified
“…Bei nur etwa 1 % aller Patienten ist der Harntrakt befallen, wobei die Endometriose am häufigsten in der Harnblase, seltener im Harnleiter und am seltensten in der Niere auftritt (2,3,8,9,13,15,16,22,23,27,31,32).…”
Section: Introductionunclassified
“…Der beidseitige Befall des Harnleiters ist eine ausgesprochene Rarität; seit 1917 wurde in der englischsprachigen Literatur lediglich 11mal darüber berichtet (6,12,16,23,25,30,31,34 Die Therapie der Harnleiterendometriose erfolgt entweder operativ, hormonell oder kombiniert. Die Entscheidung darüber kann nur individuell getroffen werden und hängt von verschiedenen Faktoren ab, wie dem Ausmaß des Endometriosebefalles, dem Alter der Patientin, der lokalen und allgemeinen Operabilität, der Funktion der betroffenen und der kontralateralen Niere, der wahrscheinlichen Compliance der Patientin bei längerer konservativer Therapie und der Akzeptanz der Nebenwirkungen einer Hormonbehandlung.…”
Section: Introductionunclassified